Youth Against Intolerance (Journal of Parents and Teachers, 2025)
The article is carried out by young people who seek to create a plural movement to promote an educational style that fosters tolerance, solidarity, and values, as well as the absence of discrimination and violence. For this reason, a campaign is formed that encourages all young people to be a part of it, since 1995 is the Year of Tolerance.
Keywords: tolerance; youth; campaign; promote